2020
DOI: 10.1007/s40843-019-1286-1
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-supported metal single-atom catalysts: a concise review

Abstract: Single-atom catalysts (SACs) have become an emerging frontier trend in the field of heterogeneous catalysis due to their high activity, selectivity and stability. SACs could greatly increase the availabilities of the active metal atoms in many catalytic reactions by reducing the size to single atom scale. Graphene-supported metal SACs have also drawn considerable attention due to the unique lattice structure and physicochemical properties of graphene, resulting in superior activity and selectivity for several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 116 publications
1
37
0
Order By: Relevance
“…However, scientists also found that single-atom catalysts were not easily prepared. An effective strategy is to deposit the ultra-small metal nanoparticles on the carbon surface or dope the metal atoms in the carbon framework to produce a so-called single-atom-like catalyst (Gawande et al, 2020;Ren et al, 2020). As expected, the single metal atom-decorated (deposited/doped) carbon catalysts illustrated excellent catalytic performances on oxygen reduction reaction (Wang et al, 2020b;Ren et al, 2020), oxygen evolution reaction (Hou et al, 2019;Wang et al, 2020b), hydrogen evolution reaction (Zhang et al, 2019d;Ren et al, 2020), CO 2 reduction reaction (Wang et al, 2019a;Lu et al, 2019;Yang et al, 2019), and nitrogen electroreduction (Chen et al, 2018b), etc.…”
Section: Introductionmentioning
confidence: 61%
“…However, scientists also found that single-atom catalysts were not easily prepared. An effective strategy is to deposit the ultra-small metal nanoparticles on the carbon surface or dope the metal atoms in the carbon framework to produce a so-called single-atom-like catalyst (Gawande et al, 2020;Ren et al, 2020). As expected, the single metal atom-decorated (deposited/doped) carbon catalysts illustrated excellent catalytic performances on oxygen reduction reaction (Wang et al, 2020b;Ren et al, 2020), oxygen evolution reaction (Hou et al, 2019;Wang et al, 2020b), hydrogen evolution reaction (Zhang et al, 2019d;Ren et al, 2020), CO 2 reduction reaction (Wang et al, 2019a;Lu et al, 2019;Yang et al, 2019), and nitrogen electroreduction (Chen et al, 2018b), etc.…”
Section: Introductionmentioning
confidence: 61%
“…The utilization rate of metal atoms can be improved by reducing the size of metals to create more metal sites. Generally, the utilization rate of metal atoms reaches the maximization when the size of metals is decreased to a single atom [27–29] . In addition, the quantum size effects and interactions between the single metal atom and the supports in the single‐atom catalysts (SACs) not only can further boost the catalytic activity, but also can achieve outstanding stability owing to the uneasy aggregation of single atoms confined by the supports [30,31] .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the utilization rate of metal atoms reaches the maximization when the size of metals is decreased to a single atom. [27][28][29] In addition, the quantum size effects and interactions between the single metal atom and the supports in the singleatom catalysts (SACs) not only can further boost the catalytic activity, but also can achieve outstanding stability owing to the uneasy aggregation of single atoms confined by the supports. [30,31] Moreover, the catalytic performance derived from SACs is more approximate to the theoretical calculation results, where an atomic structure theoretical model must be established when conducting the theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, reserves and cost issues hinder the widespread use of precious metal catalysts, despite their excellent activity and selectivity. Metal‐free heteroatoms‐doped carbon materials were first studied as alternatives to replace precious metal catalysts for the four‐electron ORR in fuel cells due to their abundant reserves and superb activities [ 28–33 ] However, research subsequently proved that the high overpotential of the carbon‐based materials toward ORR was due to its relatively high selectivity to H 2 O 2 , [ 34,35 ] which led to growing attention focusing on their selective production of H 2 O 2 . However, high ORR overpotential of carbon‐based material in the acid medium still matters despite H 2 O 2 superior selectivity.…”
Section: Introductionmentioning
confidence: 99%